(3JfhY GdJYHjQ Yf Mbhb GdeQCI h hGLHGJgG ai GdbQBf GdcQje (B/ s - (3gHI Gddg MSGfjf MSjfs; (3MSf LGO WHd (B: s ((3GdbGgQI (B: s (3gHI Gddg MSGfjf MSjf (B: s, 2019)
(3JJchf GdQSGdI ef(B: (3GdebOeI(B: (3h JTed GdMOjK Yf CSHGH GNJjGQ GdehVhY(B: (3h Cge GdOQGSGJ GdSGHbI(B: (3h NWI GdOQGSI(B: (3h efgLgG(B. (3GdJegjO(B:(3Hjf GdeQCI ehGVYGJ GdEfSGf h gOi GdbQBf(B. (3h jJfGhd GdMOjK Yf ecGfI GdeQCI ai GdESdGe ebGQfI HeG cGfJ Ydjg bHd XghQ GdESdGe h HeG UGQJ Edjg ai GdYUQ GdMGVQ(B. (3GdaUd GdChd(B: (3GdGNJjGQ GdeYLei(B. (3h jTed eHMKjf; GdeHMK GdChd(B: (3ai GNJjGQ GdJSejI, h GdeHMK GdKGfi(B: (3ai JbQjQ GdMbhb h GdhGLHGJ(B. (3GdaUd GdKGfj(B: (3GNJjGQ GdUjZI(B. (3h jTed KdGKI eHGMK(B: (3GdeHMK GdChd(B: (3GNJjGQ UjZI GdGSe, h GdeHMK GdKGfi(B: (3GNJjGQ UjZI GdaYd, h GdeHMK GdKGdK(B: (3UjZ GdeTGQcI(B. (3GdaUd GdKGdK(B: (3GNJjGQ GdCOGI(B. (3h jTed KdGKI eHGMK(B: (3GdeHMK GdChd(B: (3MQha GdLQ, h GdeHMK GdKGfi(B: (3MQha GdYWa (B((3GdaGA (B- (3oKnqe (B- (3Ch(B) (3fehPkLG, h GdeHMK GdKGdK(B: (3COhGJ GdTQW (B((3Ef(B- (3EPG(B) (3fehPkLG(B. (3GdaUd GdQGHY(B: (3GdHfGA GdJQcjHi(B. (3h jTed KdGKI eHGMK(B: (3GdeHMK GdChd(B: (3GdJbOje h GdJCNjQ, h GdeHMK GdKGfi(B: (3GdMPa h GdPcQ, h GdeHMK GdKGdK(B: (3GdGdJaGJ(B. (3GdNGJeI(B: (3h ajgG Cge eG JhUdJ Edjg GdOQGSI ef fJGFLs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdHdGZI h GdfbO GdCOHi h GdCOH GdebGQfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdbQBf GdcQjes; (3JfhY GdJYHjQs; (3Mbhb GdeQCI h hGLHGJgGs